Mechanically-induced defects in milled CdZnSe nanocrystalline powder - Bagudo, Ibrahim Muhammad (2016)
High-quality CdZnSe nanocrystals with diameters ranging from 2.6 nm to 4.3 nm were synthesized via high and low energy mechanical milling for 20 h and 100 h respectively. The XRD diffractograms of the milled powders consist of three major diffraction peaks indexed to the lattice planes (111), (002), (220) and (311) of the compound CdZnSe in the cubic phase structure. The optical spectra of the nanoparticles exhibited an onset absorption peak at 349 nm, with maximum absorption from 250-290 nm. The photoluminescence (PL) spectra exhibit broad emission bands in the wavelength range 350-900 nm. Band emissions of 1.74 eV, 1.54 eV and 1.4 eV at longer wavelengths were associated with the surface state defects. Time-resolved photoluminescence (TRPL) and photoluminescence (PL) spectroscopy measurements were carried out on mechanochemically alloyed CdZnSe nanocrystals. The TRPL emissions exhibit bi-exponential decay dynamics consisting of an initial fast component over a range of 0.05-0.87ns and a slower component (0.76-1.60 ns). The chemical nature of the mechanically induced paramagnetic defect centers induced during mechanical alloying was investigated using electron spin resonance (ESR). The ESR spectra display a faint signal at g~3.9 with a spin density of the order of ~3.34 X 104 spins/g attributed to Fe3+ introduced from the grinding medium. The intensity, linewidth and g-value of the dominant signal increase linearly with increasing milling time. The paramagnetic defect increased linearly from ~1 X 1020 spins/g to 7 X 1020 spins/g similarly, g-values increases from 1.9993(3) to 2.0026(4) and linewidth (ΔBPP) from (10.89 to 40.27) mT. The center is believed to consist of several overlapping signals arising from different paramagnetic centers present in the milled sample with Zni-VZn predominant. The low temperature PL analyses indicate that the optical transition that gave rise to the peak at high photon energy involves an electron trapped at donor defect and hole trapped at an acceptor in association with residual impurities from the grinding medium (VZn-X), where X represents residual impurities. The large blue shift in the energy band gap of the milled samples involved Burstein-Moss effects and transitions due to trapped charge carriers. The high-resolution transmission electron microscopy (HRTEM) histogram reveals that the centre of size distribution was 3.50, 2.66, and 2.00 nm for samples milled for 5 h, 10 h and 20 h respectively. High-transmission electron microscopy (HRTEM) revealed the successful annihilation of such defects with continuous milling. Stoichiometric defect due to slow diffusion of zinc has been identified as the major source of defect. The most probable induced centers during mechanical milling were (VZn–Zni), VZn, and VCd.